2012
DOI: 10.53841/bpsecp.2012.29.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Pupil wellbeing – Teacher wellbeing: Two sides of the same coin?

Abstract: There is now a strong body of evidence (e.g. Hattie, 2009; Roorda et al., 2011) that confirms the value of positive teacher-student relationships for learning and behaviour. The quality of relationships in a school, however, also impacts on teacher wellbeing and their ability to cope well with the many and varied stresses that are the hallmarks of the profession. Teacher attrition is a major concern in the Western world – how teachers feel makes a difference to their ability to respond effectively to the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(74 citation statements)
references
References 22 publications
1
44
0
2
Order By: Relevance
“…In the field of education, teachers' wellbeing affects the learning environment and students' wellbeing. Wellbeing is experienced when an individual feels valued and cared for, is not overloaded, and experiences job stimulation and enjoyment (Roffey, 2012). Collie and Martin (2017) found that the ability to adjust under stressful circumstances positively influences the wellbeing of pre-tertiary teachers.…”
Section: Resilience As a Contributor To Wellbeingmentioning
confidence: 99%
“…In the field of education, teachers' wellbeing affects the learning environment and students' wellbeing. Wellbeing is experienced when an individual feels valued and cared for, is not overloaded, and experiences job stimulation and enjoyment (Roffey, 2012). Collie and Martin (2017) found that the ability to adjust under stressful circumstances positively influences the wellbeing of pre-tertiary teachers.…”
Section: Resilience As a Contributor To Wellbeingmentioning
confidence: 99%
“…The notion of diversityrelated well-being pedagogy develops the aspect that students' well-being is interwoven with teachers' well-being (Norozi and Ness, in press). Teachers can consider students' well-being as an integral part of their work if only they themselves experience wellbeing (Roffey, 2012;Norozi and Ness, in press).…”
Section: Well-being Of Teachers Who Work With Newcomersmentioning
confidence: 99%
“…About a third of the studies in this review put forward school climate as an essential enabling factor for social capital. School leaders are encouraged to build an atmosphere of trust and respect between teachers (Anderson, 2008;high WoE;Dudley, 2013;mid WoE) and promote teacher wellbeing (Qvortrup, 2016;mid WoE) to improve teacher retention (Fagerlind et al, 2013;Qvortrup, 2016;Roffey, 2012; all mid WoE) and student wellbeing (Roffey, 2012;mid WoE). The argument is that teacher and student wellbeing are two sides of the same coin, which means that schools should support teachers' wellbeing to promote wellbeing for students (Roffey, 2012;mid WoE).…”
Section: School Climate (21)mentioning
confidence: 99%
“…School leaders are encouraged to build an atmosphere of trust and respect between teachers (Anderson, 2008;high WoE;Dudley, 2013;mid WoE) and promote teacher wellbeing (Qvortrup, 2016;mid WoE) to improve teacher retention (Fagerlind et al, 2013;Qvortrup, 2016;Roffey, 2012; all mid WoE) and student wellbeing (Roffey, 2012;mid WoE). The argument is that teacher and student wellbeing are two sides of the same coin, which means that schools should support teachers' wellbeing to promote wellbeing for students (Roffey, 2012;mid WoE). A supportive learning climate is also vital for enabling new teachers to access and build social capital, which will affect both performance and professional competence (Civis et al, 2019;high WoE) A trusting school climate that allows teachers to try out novel ideas is also beneficial for the implementation, and pedagogical use, of new technology (Li and Choi 2014;high WoE), and 'social capital cannot be infused nor can it be enacted from external authorities; rather, it can only be nurtured over time from within the school organization.'…”
Section: School Climate (21)mentioning
confidence: 99%